Polymeric nanoparticles methods of preparation and drug release models: effectiveness towards drug delivery system - Chaudhry, Gul-e-Saba; Akim, Abdah; Yik Sung, Yeong; Tengku Muhammad, Tengku Sifzizul (Research Journal of Pharmacy and Technology, 2022)
Cancer faces significant problem in disease treatment. The conventional drug has the potential to kill cancer cells but its causes severe side effects. Due to nanotechnology advancements, various drug formulations are developed, which display a remarkable difference in the effectiveness of chemotherapeutics in cancer treatment. Various drug delivery systems showed potent drug release mechanisms that reduce the potential side effects of conventional drugs. The polymeric nanoparticles formulations can regulate the pharmacological properties of anticancer drug positively. The method of polymeric nanoparticle synthesis is utmost important as it deals with various physico-chemical properties of delivery system. These properties regulate the development of effective therapeutics in the treatment of cancer. The polymeric nanoparticle morphology and physiological characteristics, including drug release kinetics, should investigated thoroughly to minimize the potential disadvantages of the delivery system. The method of nanoparticles and drug release kinetics effectively up-regulate the possible use of future nanotherapeutics.